Inclusiveness and Local Culinary Business Innovation Model on the Business Performance of Micro, Small, and Medium Enterprises in Serdang Bedagai Regency - Zulia Rifda Daulay; Dwi Kartika Sari (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
This study aims to analyze the influence of inclusiveness, innovation, and market orientation on the performance of Micro, Small, and Medium Enterprises (MSMEs) through competitive advantage in the local culinary sector in Serdang Bedagai Regency. The study employed a quantitative approach using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The research sample consisted of 282 respondents who were culinary MSME owners, selected through purposive sampling techniques. Data collection was conducted using questionnaires with a Likert scale.The results of the study indicate that inclusiveness, innovation, and market orientation have a positive and significant effect on competitive advantage. Innovation was found to be the most dominant variable influencing competitive advantage. Furthermore, competitive advantage and market orientation were also proven to have a positive and significant effect on MSME performance. The research model demonstrated a fairly strong explanatory power, with an R-square value of 0.286 for the MSME performance variable.This study implies that improving MSME performance can be achieved through strengthening inclusive access, fostering innovation development, and enhancing understanding of market needs in order to create sustainable competitive advantage.